Investigation of mechanical behavior of wood polymer nanocomposites (WPNs) samples using static vickers microhardness tester - Aşikuzun, Elif; Kaymakci, Alperen (Kastamonu University, 2018)
Aim of study: In this study, XRD and Vickers microhardness analyses of wood polymer
nanocomposites (WPNs) materials are carried out in detail. Especially, we are focused on the mechanical
analysis.

Area of study: Pine wood flour (40 mesh) as lignocellulosic filler obtained from a
commercial WPC manufacturer (sema wood) in Tekirdag, Turkey are used.

Material and Methods: Polypropylene, nano TiO2 and coupling agent
are used in the experiments. Depending on the nanocomposite groups, granulated
polymer, wood flour, nano TiO2 and MAPP are mixed. Then this mixture
is compounded in a laboratory scale twin-screw extruder at 40 rpm screw speed.

Main results: According to the obtained hardness results, all of the materials show RISE
(Reverse Indentation Size Effect) behavior. Experimental microhardness results
are compared with the mathematical models (Meyer's law, Proportional sample
Resistance (PSR), Elastic/Plastic Deformation (EPD) and Indentation-Induced Cracking (IIC) models) used in the microhardness analysis of materials in the
literature and the most suitable model for microhardness values of materials
was determined. According to the models, IIC model is the most
suitable to determine the micromechanical properties.

Research highlights: Structural and mechanical properties of WPNs materials are investigated. The increase in
the microhardness values of the all sample depends on the increase of applied
load. In addition, the microhardness values decrease with
increased TiO2 concentration in the samples and microhardness
values reach a saturation region at around for the samples.
Keywords: WPNs; Vickers microhardness; IIC model; RISE; XRD; WPN; Vickers mikrosertlik; IIC modeli; RISE; XRD